The Validity and Reliability of Box and Blocks Test on Children with Traumatic Elbow Injury - Tamboosi, Mohammad; Tamboosi, Sara; Fasihaldeen, Abdulraouf; Bashraheel , Jana; Alnajjar , Moaaz; Melibary , Raghad; Bamehriz, Yazeed (J Med Rehab Sci, 2025)
INTRODUCTION: The Box and Blocks Test (BBT) is a widely used measure of manual dexterity, but its validity and reliability as an outcome measure for upper extremity function in children with Traumatic Elbow Injuries (TEI) require further investigation. This study aimed to evaluate the BBT's test-retest reliability, sensitivity to functional change (construct validity), and discriminative validity in this specific pediatric population. METHOD: Twenty-nine children (75.9% male; age range: 6-16 years) with TEI participated in a prospective study. BBT scores for both hands were assessed pre- and post- an eight-week physiotherapy intervention. Test-retest reliability was evaluated via Cronbach's Alpha, and discriminative validity using Receiver Operating Characteristic (ROC) curve analysis of pre-intervention scores. RESULTS: Excellent test-retest reliability was found (Cronbach's Alpha = 0.991). Significant improvements in BBT scores occurred post-intervention for both right (p<0.001) and left hands (p<0.001), indicating sensitivity to change. However, discriminative validity of pre-intervention BBT was limited, with low Area Under the Curve (AUC) values (Right: 0.435, Left: 0.425). These AUCs suggest the test performed worse than random chance in differentiating specified outcomes at baseline. CONCLUSION: The BBT is a sensitive and reliable tool for detecting functional improvements in children with TEI post-physiotherapy. Its limited discriminative validity at baseline warrants cautious interpretation. Future research with larger, diverse samples should investigate age and gender effects, and explore broader functional outcomes to fully establish BBT's comprehensive role as an assessment tool in this population.